The role of CT in prognosis prediction in COVID-19 patients - Tonje Gravdal; Kine Storås; Albertina Rusandu; Ragna Stalsberg (Radiography Open)
Introduction: The aim of the present study was to summarize and evaluate previously published scientific studies examining whether computed tomography (CT) of the thorax can predict the COVID-19 prognosis. The purpose is to clarify whether CT can predict the COVID-19 prognosis, and also if a CT examination can predict whether the patient will be admitted to the intensive care unit (ICU) or not.